2017
DOI: 10.1159/000486013
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Plasma Homocysteine and Microalbuminuria in Untreated Patients with Essential Hypertension: a Case-Control Study

Abstract: Background/Aims: Kidney function is critical for homocysteine (Hcy) clearance, and plasma Hcy levels are frequently increased in patients with renal failure. Microalbuminuria (MAU) is an important marker of early renal damage caused by hypertension. At present, there is insufficient evidence on the relationship between Hcy and microalbuminuria. Methods: This is a 1: 2 matched, hospital-based case-control study. At initial visit, out of 1535 outpatients with no prior history of medication, 450 qualified subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Homocysteine is a sulphur-containing non-proteinogenic amino acid biosynthesized from methionine and abnormal elevation of circulating homocysteine concentrations has been implicated in the development of many clinical end-points or pathological conditions, such as cardiovascular disease, 15 stroke 16 and microalbuminuria. 17 Hyperhomocysteinaemia is an independent risk factor for glomeruloslerosis and renal insufficiency and the association of circulating homocysteine with DKD was widely evaluated in the medical literature, yet the results are not often reproducible. [7][8][9][18][19][20][21][22] Actually, current evidence linking homocysteine to DKD is mainly based on observational data, in which the degree of possible confounding and reverse causation may cloud the true relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Homocysteine is a sulphur-containing non-proteinogenic amino acid biosynthesized from methionine and abnormal elevation of circulating homocysteine concentrations has been implicated in the development of many clinical end-points or pathological conditions, such as cardiovascular disease, 15 stroke 16 and microalbuminuria. 17 Hyperhomocysteinaemia is an independent risk factor for glomeruloslerosis and renal insufficiency and the association of circulating homocysteine with DKD was widely evaluated in the medical literature, yet the results are not often reproducible. [7][8][9][18][19][20][21][22] Actually, current evidence linking homocysteine to DKD is mainly based on observational data, in which the degree of possible confounding and reverse causation may cloud the true relationship.…”
Section: Discussionmentioning
confidence: 99%
“…An animal study implicated elevated Hcy related to glomerular injury [ 26 ]. In both essential hypertension and general adult populations, high Hcy was associated with albuminuria independent of renal function [ 27 , 28 ]. A prospective study showed that Hcy was an independent determinant of the development of albuminuria even after adjustment for eGFR [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] HHcy has been identified as a risk factor of CKD and contributes to cardiovascular complications. [6][7][8][9] A cross-sectional survey reveals that hypertension is a major cause of CKD, 10 but the molecular mechanisms by which HHcy mediates hypertensionassociated kidney damage remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%